2020
DOI: 10.1007/s10902-020-00247-3
|View full text |Cite
|
Sign up to set email alerts
|

Need Satisfaction and Optimal Functioning at Leisure and Work: A Longitudinal Validation Study of the DRAMMA Model

Abstract: In recent years, there has been an increasing interest in psychological need satisfaction and its role in promoting optimal functioning. The DRAMMA model integrates existing need and recovery models to explain why leisure is connected to optimal functioning (i.e., high well-being and low ill-being). It encompasses six psychological needs: detachment, relaxation, autonomy, mastery, meaning, and affiliation (DRAMMA). While the individual needs of the DRAMMA model have been previously shown to relate to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 78 publications
4
39
0
1
Order By: Relevance
“…While most of these recovery experiences relate to physiological deactivation, affect regulation, and needs satisfaction processes (e.g. Kujanpää et al, 2021), the concept of psychological detachment directly concerns work-related thoughts, on which we also focus in this special issue (Sonnentag and Fritz, 2007;Virtanen et al, 2020).…”
Section: Conceptual Definitionsmentioning
confidence: 99%
“…While most of these recovery experiences relate to physiological deactivation, affect regulation, and needs satisfaction processes (e.g. Kujanpää et al, 2021), the concept of psychological detachment directly concerns work-related thoughts, on which we also focus in this special issue (Sonnentag and Fritz, 2007;Virtanen et al, 2020).…”
Section: Conceptual Definitionsmentioning
confidence: 99%
“…For instance, strategies for finding a purpose in life turned out to be negatively related to well-being (e.g., search for meaning; Li et al, 2020; struggle with ultimate meaning; Wilt et al, 2018) or have shown both positive and negative relationships to different aspects of well-being (meaning-making; Park, 2010). In addition, research on the role of meaning and affiliation as enhancers of the recovery process beyond recovery experiences of the REQ has rendered both null and positive effects (Kujanpää et al, 2020;Virtanen et al, 2020). As meaning and affiliation at leisure time are highly culturallyand contextually-shaped experiences (Iwasaki, 2018), examining these two newer facets of recovery experiences in distinct cultural contexts is meaningful.…”
Section: Crafting For Meaning and For Affiliationmentioning
confidence: 99%
“…The DRAMMA (i.e., detachment, relaxation, autonomy, mastery, meaning, and affiliation) model addresses these objectives and integrates insights from the fields of recovery from work and leisure sciences (Newman et al, 2014;Kujanpää et al, 2020). Based on a literature review of 363 scientific articles, Newman et al (2014) proposed that six psychological experiences mediate the positive relationship between leisure and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Die Dramma-Skala [24] bildete die Basis zur Erfassung der Erholungsfähigkeit. Die 6 Bereiche Gedankenfreiheit ("detachment"), Entspannung ("relaxation"), Selbstbestimmung ("autonomy"), Herausforderung ("mastery"), Sinn ("meaning") und Verbundenheit ("affiliation") wurden durch jeweils ein Item abgefragt, welches die höchste Trennschärfe auf der jeweiligen Dimension aufwies [18]. Ein hier ins Deutsche übersetzte Beispielitem lautet "Während meiner letzten Feierabende habe ich richtig von der Arbeit abschalten können."…”
Section: Verwendete Instrumenteunclassified